2016
DOI: 10.1097/wnp.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Motor Evoked Potentials in Insular, Precental, or Postcentral Resections

Abstract: The primary motor cortex and corticospinal pathway can reliably be monitored to protect motor strength during insular, precentral, and postcentral resections under general anesthesia. Nevertheless, MEPs did not prevent subcortical ischemias that might be reduced with continuous subcortical mapping. For the preservation of complex motor functions, for example, bimanual coordination, not evaluated here, insular surgeries can be performed with awake surgeries for which decision to undergo remains to the patient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The introduction of phase reversal for the precise allocation of the central sulcus, in combination with transcranial or direct subsequent motor mapping and motor evoked potential (MEP) monitoring, has allowed to define entry zones for surgery in and around the central region and for the placement of subdural strip electrodes for continuous MEP monitoring during i.e. tumor surgery or during resective epilepsy surgical procedures in the vicinity of the somatosensory cortex [ 23 , 28 , 93 ]. Subsequent developments in monitoring and mapping of cerebral functions, of white matter fiber tracts, and cranial/peripheral nerves have since become a mainstay of functional preservation during neurosurgical procedures [ 29 , 45 , 46 , 79 , 81 , 114 ].…”
Section: Monitoring and Mapping In Neurosurgerymentioning
confidence: 99%
“…The introduction of phase reversal for the precise allocation of the central sulcus, in combination with transcranial or direct subsequent motor mapping and motor evoked potential (MEP) monitoring, has allowed to define entry zones for surgery in and around the central region and for the placement of subdural strip electrodes for continuous MEP monitoring during i.e. tumor surgery or during resective epilepsy surgical procedures in the vicinity of the somatosensory cortex [ 23 , 28 , 93 ]. Subsequent developments in monitoring and mapping of cerebral functions, of white matter fiber tracts, and cranial/peripheral nerves have since become a mainstay of functional preservation during neurosurgical procedures [ 29 , 45 , 46 , 79 , 81 , 114 ].…”
Section: Monitoring and Mapping In Neurosurgerymentioning
confidence: 99%
“…This is similar to the application of different alarm criteria for transcranial as opposed to direct cortical stimulation during the resection of insular, pre-, or postcentral lesions. 26 Dong et al 24 and Matthies et al 17 also found a lower alarm criterion, that is, a 35% decrease in MEP amplitude, prone to trigger more warnings than with a 50% decrease in MEP amplitude, in similar and larger groups of patients. This low alarm criterion is in line with the previous observation of the high rates of poor facial nerve outcomes in the cases with a 50% decrease in MEP amplitude.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, Ostry et al [ 42 ] used during supratentorial tumor surgery a threshold increase >2 mA not as an indicator for surgical intervention but for the performance of subcortical mapping. The definition of a minimum MEP amplitude to be monitored varied significantly among the papers from 10 to 100 μV with an average of 30–50 μV [ 8 , 10 , 11 , 29 , 32 , 33 , 35 , 38 , 42 , 48 , 53 , 66 , 73 , 74 , 76 , 78 ]. However, in many, it was not clearly defined.…”
Section: Discussionmentioning
confidence: 99%